2021
DOI: 10.1101/2021.01.27.428353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of SARS-CoV-2 spike mutations on animal ACE2 usage and in vitro neutralization sensitivity

Abstract: Spontaneous and selection-pressure-driven evolution of SARS-CoV-2 has started to pose more challenges to controlling the pandemic. Here, we first investigated cross-species receptor usage of multiple SARS-CoV-2 variants that emerged during the pandemic. We found that, in contrast to an early isolate WHU01, the circulating variants B.1.1.7/501Y.V1, B.1.351/501Y.V2, and P.1/501Y.V3 were able to use rat and mouse Ace2 orthologs as entry receptors, suggesting that rats and mice might be able to harbor and spread t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 69 publications
2
25
0
Order By: Relevance
“…While it has been shown that mutations result in more fit, and likely more contagious viruses (15,16,40), the serological consequences of the mutations found in VOC are unclear (40). Recent studies have shown reduced binding to therapeutic antibodies or Spike-specific antibodies for the circulating VOC B.1.1.7, 501Y.V2 and P.1 in vitro (41,42). All three VOC harbor an N501Y mutation within S-RBD, while the 501Y.V2 and P.1 variants contain two additional RBD changes, K417N/T and E484K.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that mutations result in more fit, and likely more contagious viruses (15,16,40), the serological consequences of the mutations found in VOC are unclear (40). Recent studies have shown reduced binding to therapeutic antibodies or Spike-specific antibodies for the circulating VOC B.1.1.7, 501Y.V2 and P.1 in vitro (41,42). All three VOC harbor an N501Y mutation within S-RBD, while the 501Y.V2 and P.1 variants contain two additional RBD changes, K417N/T and E484K.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it might be possible to extend our data into the increased ACE2 receptor binding affinities of circulating variant viruses 3537 . A hypothesis would be that these viruses can infect the upper respiratory tract, in which ACE2 is scarce, more efficiently leading to increased transmission, a highly similar model as observed for human influenza A viruses 38,39 .…”
Section: Discussionmentioning
confidence: 93%
“…55,56 Moreover, neutralizing monoclonal antibody therapies may have reduced effects on some naturally existing SARS-CoV-2 variants. 57 For example, while B.1.1.7 variant normally did not influence antibody neutralizing ability, B.1.351 and P.1 variants were partially resistant to casirivimab and completely resistant to bamlanivimab in vitro. 41,[57][58][59] In light of the markedly increasing spread of SARS-CoV-2 variants potentially resistant to bamlanivimab, the US government has halted distribution of bamlanivimab monotherapy on 24 March 2021, and the US FDA retracted the EUA of bamlanivimab monotherapy on 16 April 2021.…”
Section: Neutralizing Monoclonal Antibodiesmentioning
confidence: 97%
“…57 For example, while B.1.1.7 variant normally did not influence antibody neutralizing ability, B.1.351 and P.1 variants were partially resistant to casirivimab and completely resistant to bamlanivimab in vitro. 41,[57][58][59] In light of the markedly increasing spread of SARS-CoV-2 variants potentially resistant to bamlanivimab, the US government has halted distribution of bamlanivimab monotherapy on 24 March 2021, and the US FDA retracted the EUA of bamlanivimab monotherapy on 16 April 2021. 60,61 The combination use of two or more potent monoclonal antibodies targeting noncompeting sites on SARS-CoV-2 may reduce the possibility of virus resistance and mutational escape.…”
Section: Neutralizing Monoclonal Antibodiesmentioning
confidence: 97%